Evaluation of the quantitative performance of non-enhanced dual-energy CT X-map in detecting acute ischemic brain stroke: A model observer study using computer simulation - Itoh, Toshihide; Noguchi, Kyo (Physica medica, 2022)
[Display omitted] •Simulation study evaluated effectiveness of X-map + CHO in detecting ischemic edema.•We compared NE-DECT X-map images with NE-DECT mixed images.•X-map images showed better detectability at all edema densities & radiation doses.•Detectability of edema in mixed and X-map images differed based on GM/WM proportions.•NE-DECT X-map may improve identification & quantification of ischemic edema in AIS. A simulation study was performed to evaluate the quantitative performance of X-map images—derived from non-enhanced (NE) dual-energy computed tomography (DECT)—in detecting acute ischemic stroke (AIS) compared with that of NE-DECT mixed images. A virtual phantom, 150 mm in diameter, filled with tissues comprising various gray- and white-matter proportions was used to generate pairs of NE-head images at 80 kV and Sn150 kV at three dose levels (20, 40, and 60 mGy). The phantom included an inserted low-contrast object, 15 mm in diameter, with four densities (0%, 5%, 10%, and 15%) mimicking ischemic edema. Mixed and X-map images were generated from these sets of images and compared in terms of detectability of ischemic edema using a channelized Hotelling observer (CHO). The area under the curve (AUC) of the receiver operating characteristic that generated CHO for each condition was used as a figure of merit. The AUCs of X-map images were always significantly higher than those of mixed images (P < 0.001). The improvement in AUC for X-map images compared with that for mixed images at edema densities was 9.2%-12.6% at 20 mGy, 10.1%-17.7% at 40 mGy, and 14.0%-19.4% at 60 mGy. At any edema density, X-map images at 20 mGy resulted in higher AUCs than mixed images acquired at any other dose level (P < 0.001), which corresponded to a 66% dose reduction on X-map images. The simulation study confirmed that NE-DECT X-map images have superior capability of detecting AIS than NE-DECT mixed images.